2020
DOI: 10.1111/fcp.12611
|View full text |Cite
|
Sign up to set email alerts
|

SIS3, a good candidate for the reverse of type 2 diabetes mellitus in mice

Abstract: TGF‐β signaling plays an extremely important role in the occurrence and development of type 2 diabetes mellitus (T2DM), and the blockade of TGF‐β/Smad3 pathway protests against the high‐fat diet‐induced obesity and diabetes. As a specific small molecule inhibitor of Smad3 protein, the biological activities of compound SIS3 were evaluated by high‐fat diet‐induced T2DM model mice. In vivo results indicated that SIS3 can not only significantly reduce the body weight, fat mass, and fasting blood glucose in high‐fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Therefore, exploration of Smad3-targeted expression modification or chemical inhibitors may be promising approaches for the treatment of T2DM. Recently, it is reported that administration of SIS3, a specific inhibitor of Smad3, in HFD-fed mice reduces body weight and hyperglycemia with improved glucose intolerance and insulin resistance [115]. Our unpublished data also suggests a protective role of SIS3 against diabetic phenotype with improved β cell survival in db/db mice.…”
Section: Conclusion Perspectives and Future Directionssupporting
confidence: 65%
“…Therefore, exploration of Smad3-targeted expression modification or chemical inhibitors may be promising approaches for the treatment of T2DM. Recently, it is reported that administration of SIS3, a specific inhibitor of Smad3, in HFD-fed mice reduces body weight and hyperglycemia with improved glucose intolerance and insulin resistance [115]. Our unpublished data also suggests a protective role of SIS3 against diabetic phenotype with improved β cell survival in db/db mice.…”
Section: Conclusion Perspectives and Future Directionssupporting
confidence: 65%